Nicanor Parra: antipoems, parodies and hybrid languages, the language of the artifact antipoetry - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Strictly separate disciplines before, art history, literary criticism, sociology, political science and history, begin to look at their boundaries blurred and crossed in a particular class of hybrid and transversal studies, which were no longer easily assigned to one domain or another. Giving rise to a new discursive phenomenon, which can only be designated generically-as-theory (theory). The original form of these works reflects, as we shall see, the increasing textualization of its objects, showing a resurgence, but much more versatile, the ancient practice of "comment" kind, like the "after-dinner speech" Nicanor Parra, subscribe. In Parra-Cervantes Prize 2011, the highest honor and most important literary award in Spanish-we have one of the most outstanding examples of these deconstructive writings, with its clear emphasis on narrative as a foundation instance of postmodern reason. Parra exceeds the bounds of canonical language, the "sacred cow poetry-in a clear allusion to Neruda irreverent and stages its special" artifacts dramatic, "morpho-syntactic exercises that cross object and allow text and field projection of experience, a visual language, whose material and texture are the disturbing object which we call "artifact". Antipoetry is thus in the deconstructive project Parra, a contratexto, or counter-lyrical intonations urban ecological erotológicas, political, eschatological, and so on., Where Neruda and I speak the nature of heroic gestures, but the modern subject, ironic and sarcastic, which has fragmented monologue confessional nudity a clinical document and intellectual development